Electronic word of mouth, price, store atmosphere, and brand image on food purchasing decisions - Gede Feby Suarjaya Putra (Universitas Pendidikan Nasional, 2025)
This research aims to the culinary business is an activity of producing F&B that aims to be sold to consumers in the hope of getting the maximum possible profit. Kober Mie Setan Branch of Dewi Sri is a well-known culinary business in Bali. Instagram is used by Kober Mie Setan, Dewi Sri Branch to promote the products it sells using the electronic word- of-mouth method. Communication via the internet was carried out by Kober Mie Setan, Dewi Sri Branch, to discuss product issues, one of which was price. Prices are inseparable from the store atmosphere. Mie Setan Kober created a new slogan, namely